Composite curing agent for curing chlorine and sulfur in microwave thermal conversion of macromolecular wastes as well as preparation method and application of composite curing agent

By using composite curing agents in microwave thermal conversion of polymer waste, using components such as aluminosilicate and alkali metal calcium to catalyze the curing of chlorosulfur elements in microwave electromagnetic fields, the problems of difficulty in synergistic curing of chlorosulfur in the prior art are solved, and efficient and low-cost curing of chlorosulfur contaminated elements and pyrolytic carbon recovery are achieved.

CN119746337APending Publication Date: 2025-04-04EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411969526.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing methods for purifying chlorosulfur in polymer waste have problems such as difficulty in co-curing chlorosulfur, difficult separation of pyrolysis carbon, difficult to avoid corrosion of equipment, narrow scope of application, high raw material costs and secondary pollution.

Method used

A composite curing agent is used, which consists of aluminosilicate as the porous support and alkali metal calcium as the basic active component of chlorosulfide curing. It is coupled with one or more transition metal catalytic active components. It promotes the decomposition and transfer of chlorosulfur-containing compounds through the catalytic action of the active components in the pyrolysis in the microwave electromagnetic field, and achieves in-situ synergistic and efficient curing of chlorosulfur-contaminated elements.

Benefits of technology

It has achieved efficient in-situ curing of chlorosulfur contaminated elements, the curing rate of chlorosulfur in the element can be higher than 80%, and the pyrolytic carbon can be efficiently recycled, with low raw material costs and no secondary pollution or equipment corrosion problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of polymer waste treatment, and discloses a composite curing agent for curing chlorine and sulfur in polymer waste microwave thermal conversion and a preparation method and application thereof, and the method comprises the following steps: dissolving calcium nitrate and aluminum nitrate in deionized water to form an active component I solution; dissolving at least one of zinc nitrate, copper nitrate, ferric nitrate, manganese nitrate and cerium nitrate as an active component II in the active component I solution, adding citric acid into the formed mixed solution to form gel, and drying to obtain an active matter; and mixing the active matter, silicon carbide and bentonite, ball-milling, extruding and granulating, and calcining to obtain the composite curing agent. The composite curing agent disclosed by the invention can efficiently recover pyrolytic carbon, pyrolytic oil and pyrolytic gas while effectively and synergistically curing chlorine and sulfur pollution elements in situ; the curing rate of the chlorine / sulfur element can reach 80%, the recovery rate of the composite curing agent can reach 98%, and meanwhile, the raw material cost is low, and the problems of secondary pollution and equipment corrosion are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high molecular waste treatment, and in particular to a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of high molecular waste, and a preparation method and application thereof. Background Art

[0002] As an energy field, microwaves have the characteristics of rapid, uniform and selective heating. Microwave pyrolysis is an environmentally friendly and efficient waste treatment technology, which is widely used in thermal treatment fields such as biomass, waste plastics, and toxic waste. Based on the overall microwave heating method, microwave pyrolysis can solve the problem of limited heat transfer due to the poor thermal conductivity of polymer waste and improve the pyrolysis efficiency. However, the content of chlorine and sulfur pollution elements in polymer waste is significant, resulting in pollution risks in thermal conversion products, especially pollutants related to chlorine and sulfur (hydrogen chloride, hydrogen sulfide, sulfur dioxide, polychlorinated biphenyls, dioxins, etc.); at the same time, its physical and chemical properties change significantly, resulting in low quality of pyrolysis products, which limits its clean and efficient resource utilization. By adjusting the process parameters, conventional pyrolysis can reduce the chlorine content in the pyrolysis products, but it will inevitably produce pollutants such as hydrogen chloride, hydrogen sulfide, organic chlorides, and organic sulfides.

[0003] By adding a curing agent of heteroelements, the relevant pollutants can be cured in situ, which can effectively control pollution at the source. However, the existing curing agents and pyrolysis technologies are difficult to adapt to complex polymer wastes, especially the synergistic curing of multiple heteroelements. For example, the initial removal effect of calcium oxide curing agents is obvious, but due to the phenomenon of being sensitive to humidity and easy to harden, the curing agent removal effect is not high. At the same time, because most additives are powders, it is difficult to separate pyrolytic carbon from additives, and it is impossible to achieve high-value utilization of pyrolytic carbon, which significantly reduces the effectiveness of resource recycling.

[0004] Therefore, there is an urgent need for a chlorine-sulfur composite curing agent that can efficiently and synergistically solidify chlorine and sulfur elements, has separable pyrolytic carbon, high-quality pyrolytic oil, and a wide range of applications. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the defects of the existing high molecular waste chlorine and sulfur element purification method, such as the difficulty of chlorine and sulfur synergistic solidification, the difficulty of separating pyrolytic carbon, the difficulty of avoiding equipment corrosion, the narrow scope of application, the high cost of raw materials, and the difficulty of solving secondary pollution, and provide a composite curing agent for chlorine and sulfur solidification in microwave thermal conversion of high molecular waste and its preparation method and application. The present invention belongs to the method of in-situ solidification of chlorine and sulfur elements, which is applicable to chlorine-containing and sulfur-containing components, organic and inorganic sources, and efficiently recovers pyrolytic carbon while efficiently solidifying chlorine and sulfur pollution elements in situ, and has the problems of low raw material cost, no secondary pollution, and no equipment corrosion.

[0006] To achieve the above object, on the one hand, the present invention provides a method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste, which comprises the following steps:

[0007] S1. Calcium nitrate and aluminum nitrate are used as active component I, and the active component I is dissolved in deionized water to form an active component I solution, wherein the molar ratio of calcium nitrate to aluminum nitrate is 1:1 to 1:2;

[0008] S2, using at least one of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate and cerium nitrate as active component II, dissolving active component II in the active component I solution of step S1, stirring and mixing to form a mixed solution of active components I and II, wherein the molar ratio of active component I to active component II is 1:0.5 to 1:0.1;

[0009] S3, adding chelating agent citric acid to the mixed solution of step S2, stirring and mixing to form a gel, and then drying to obtain an active substance, wherein the molar ratio of active component I to citric acid is 1:1 to 1:2;

[0010] S4, the active material of step S3, the microwave absorbing component silicon carbide and the binder bentonite are mixed uniformly according to a certain mass percentage, and ground in a ball mill to obtain a uniformly mixed molding raw material, wherein, by mass percentage, the active material is 60-85%, the microwave absorbing component silicon carbide is 10-30%, and the binder bentonite is 5-10%;

[0011] S5, the molding raw materials in step S4 are subjected to extrusion granulation and then calcined to obtain a composite curing agent.

[0012] Preferably, the active component I in step S1 is dissolved in 5 to 10 times the mass of deionized water; and / or, the chelating agent citric acid in step S3 is first dissolved in 5 to 10 times the mass of deionized water and then added to the mixed solution in step S2.

[0013] Preferably, the temperature of the deionized water for dissolving active component I in step S1 is 60-70°C, the temperature of the active component I solution for dissolving active component II in step S2 is 60-70°C, the temperature of the mixed solution in step S3 is 90-95°C, and the drying temperature in step S3 is 105-115°C.

[0014] Preferably, in step S4, the rotation speed of the ball mill is 300 to 500 r / min, and the grinding time is 10 to 30 min.

[0015] Preferably, in step S5: the particle size of the granulation is 3 to 5 mm; and / or the calcination temperature is 800 to 900° C., and the calcination time is 2 to 4 hours.

[0016] Preferably, in step S1, the molar ratio of calcium nitrate to aluminum nitrate is 1:1; and / or, in step S2, the molar ratio of active component I to active component II is 1:0.5; and / or, in step S3, the molar ratio of active component I to citric acid is 1:1.5; and / or, in terms of mass percentage, the amount of each component in the molding raw material is: 80% active material, 15% absorbing component silicon carbide, and 5% binder bentonite.

[0017] Preferably, in step S2, active component II is two of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate and cerium nitrate, and the molar ratio is 1:1.

[0018] According to another aspect of the present invention, the present invention further provides a composite curing agent, which is prepared by the above method.

[0019] According to another aspect of the present invention, the present invention also provides an application of a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste.

[0020] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0021] The composite curing agent (also known as chlorine-sulfur composite curing agent) of the present invention uses aluminosilicate as a porous carrier, alkali metal calcium as a chlorine-sulfur curing basic active component I, and is coupled with one or more transition metal catalytic active components II. In a microwave electromagnetic field, the catalytic action of the active components in pyrolysis promotes the decomposition and transfer of chlorine-sulfur compounds, and then reacts with component I to form calcium chloride or calcium sulfide, wherein some metals in the active component II will also react to form chlorides or sulfides, thereby realizing in-situ synergistic and efficient curing of chlorine-sulfur polluting elements, and the curing rate of chlorine-sulfur elements can be higher than 80%, and in some preferred embodiments can be higher than 95%; the used composite curing agent particles can be recovered by simple screening, and further regenerated and recycled, while avoiding the curing agent residue affecting the quality of pyrolytic carbon, and in some preferred embodiments can even be higher than 99%; at the same time, the raw material cost of the present invention is low, and there is no problem of secondary pollution and equipment corrosion. DETAILED DESCRIPTION

[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0023] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0024] In the following examples, calcium nitrate and aluminum nitrate are respectively used as active component I, at least one of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate, and cerium nitrate is used as active component II, citric acid is used as a chelating agent, silicon carbide is used as an absorbing component, and bentonite is used as a binder. All reagents and raw materials used are commercially available.

[0025] Example 1

[0026] 16.5 g of calcium nitrate and 21.3 g of aluminum nitrate were weighed and dissolved in 200 g of deionized water at 60°C to form an active component I solution, and then 9.5 g of zinc nitrate was added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60°C water bath for 1 hour, and then 50 g of a citric acid aqueous solution containing 9.6 g of citric acid was added, and the mixture was magnetically stirred in a 90°C water bath for 3 hours to form a gel, which was dried at 105°C for 24 hours to obtain a porous active material, which was put into a ball mill with 15 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 minutes to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900°C in an air atmosphere for 4 hours to obtain a chlorine-sulfur composite curing agent.

[0027] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 95.2% and 82.7% respectively.

[0028] Example 2

[0029] Weigh 16.5g of calcium nitrate and 21.3g of aluminum nitrate, dissolve them in 200g of deionized water at 60°C to form an active component I solution, add 9.4g of copper nitrate to form a mixed solution of active component I and active component II, stir magnetically in a 60°C water bath for 1h, add 50g of citric acid solution containing 9.6g of citric acid, stir magnetically in a 90°C water bath for 3h to form a gel, and dry at 105°C for 24h to obtain a porous active material, put it into a ball mill with 20g of silicon carbide and 5g of bentonite, grind it at 300r / min for 20min to obtain a molded powder raw material, and obtain particles with an outer diameter of 3mm by extrusion molding, and then calcine at 900°C for 4h in an air atmosphere to obtain a chlorine-sulfur composite curing agent.

[0030] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 83.8% and 95.3% respectively.

[0031] Example 3

[0032] Weigh 16.5g of calcium nitrate and 21.3g of aluminum nitrate, dissolve them in 200g of deionized water at 60°C to form an active component I solution, add 12.1g of ferric nitrate to form a mixed solution of active component I and active component II, stir magnetically in a 60°C water bath for 1h, add 50g of citric acid solution containing 9.6g of citric acid, stir magnetically in a 90°C water bath for 3h to form a gel, and dry at 105°C for 24h to obtain a porous active material, put it into a ball mill with 15g of silicon carbide and 5g of bentonite, grind it at 300r / min for 20min to obtain a molded powder raw material, and obtain particles with an outer diameter of 3mm by extrusion molding, and then calcine at 900°C for 4h in an air atmosphere to obtain a chlorine-sulfur composite curing agent.

[0033] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 89.5% and 91.1% respectively.

[0034] Example 4

[0035] The difference from Example 1 is that the composition of active component II is different, and the amounts of silicon carbide and bentonite used are different.

[0036] Weigh 16.5g of calcium nitrate and 21.3g of aluminum nitrate, dissolve them in 190g of deionized water at 60°C to form an active component I solution, add 9.5g of manganese nitrate to form a mixed solution of active component I and active component II, stir magnetically in a 60°C water bath for 1h, add 48g of citric acid solution containing 9.6g of citric acid, stir magnetically in a 90°C water bath for 3h to form a gel, and dry at 105°C for 24h to obtain a porous active material, put it into a ball mill with 15g of silicon carbide and 5g of bentonite, grind it at 300r / min for 20min to obtain a molded powder raw material, and obtain particles with an outer diameter of 3mm by extrusion molding, and then calcine at 900°C for 4h in an air atmosphere to obtain a chlorine-sulfur composite curing agent.

[0037] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 92.8% and 85.3% respectively.

[0038] Example 5

[0039] 16.5 g of calcium nitrate and 21.3 g of aluminum nitrate were weighed and dissolved in 190 g of deionized water at 60° C. to form an active component I solution, 21.7 g of cerium nitrate was added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 48 g of a citric acid solution containing 9.6 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 15 g of silicon carbide and 5 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0040] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 93.6% and 91.5% respectively.

[0041] Example 6

[0042] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.8 g of zinc nitrate and 4.7 g of copper nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0043] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 98.3% and 97.1% respectively.

[0044] Example 7

[0045] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.8 g of zinc nitrate and 6.1 g of ferric nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0046] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 96.8% and 95.4% respectively.

[0047] Example 8

[0048] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.8 g of zinc nitrate and 4.8 g of manganese nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0049] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 98.8% and 86.2% respectively.

[0050] Example 9

[0051] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.8 g of zinc nitrate and 10.9 g of cerium nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0052] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 99.2% and 98.6% respectively.

[0053] Example 10

[0054] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.7 g of copper nitrate and 4.8 g of manganese nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0055] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 94.9% and 95.6% respectively.

[0056] Comparative Example 1

[0057] Weigh 16.5g of calcium nitrate and 42.6g of aluminum nitrate, dissolve them in 400g of deionized water at 60°C to form an active component I solution, stir magnetically in a 60°C water bath for 1h, add 100g of citric acid solution containing 19.2g of citric acid, stir magnetically in a 90°C water bath for 3h to form a gel, and dry at 105°C for 24h to obtain a porous active material, put it into a ball mill with 20g of silicon carbide and 10g of bentonite, grind it at 300r / min for 20min to obtain a molded powder raw material, and obtain particles with an outer diameter of 3mm by extrusion molding, and then calcine at 900°C for 4h in an air atmosphere to obtain a chlorine-sulfur composite curing agent.

[0058] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 63.6% and 39.1% respectively.

[0059] Compared with Example 6, without adding active component II, the main chlorine-sulfur-fixing effective ingredients in the composite curing agent obtained in this comparative example are calcium aluminosilicate inorganic compounds, and the active component II that plays a microwave catalytic role is lacking. The chlorine and sulfur elements are not completely released during the heat treatment process, resulting in a low curing effect.

[0060] Comparative Example 2

[0061] 8.3 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 4.8 g of zinc nitrate and 4.7 g of copper nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0062] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite curing agent, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 71.9% and 42.8% respectively.

[0063] Compared with Example 6, under the condition that the molar ratio of calcium nitrate to aluminum nitrate in active component I is 0.25:1, the content of main chlorine-sulfur curing components (calcium aluminosilicate inorganic compounds) in the composite curing agent obtained in this comparative example is low, and the chlorine-sulfur pollutants released during the heat treatment process are not completely cured, resulting in a low curing effect.

[0064] Comparative Example 3

[0065] 16.5 g of calcium nitrate and 42.6 g of aluminum nitrate were weighed and dissolved in 400 g of deionized water at 60° C. to form an active component I solution, 1.9 g of zinc nitrate and 1.9 g of copper nitrate were added to form a mixed solution of active component I and active component II, and the mixture was magnetically stirred in a 60° C. water bath for 1 h, 100 g of a citric acid solution containing 19.2 g of citric acid was added, and the mixture was magnetically stirred in a 90° C. water bath for 3 h to form a gel, which was dried at 105° C. for 24 h to obtain a porous active material, which was put into a ball mill with 20 g of silicon carbide and 10 g of bentonite, and ground at 300 r / min for 20 min to obtain a molded powder raw material, and particles with an outer diameter of 3 mm were obtained by extrusion molding, which were then calcined at 900° C. in an air atmosphere for 4 h to obtain a chlorine-sulfur composite curing agent.

[0066] The prepared composite curing agent was subjected to a performance test experiment. The reaction conditions were: 10 g of high molecular waste (chlorine and sulfur content were 2.1% and 1.3% respectively), 10 g of composite additive, 900 W of microwave power, 600 ° C of pyrolysis temperature, 30 min of treatment, and the curing rates of chlorine and sulfur were 75.7% and 63.4% respectively.

[0067] Compared with Example 6, under the condition that the molar ratio of active component I to active component II is 1:0.05, the content of microwave catalytic active component II in the composite curing agent obtained in this comparative example is relatively low, and the chlorine and sulfur elements are not completely released during the heat treatment process, resulting in a low curing effect.

[0068] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste, characterized in that: The following steps are involved: S1. Calcium nitrate and aluminum nitrate are used as active component I, and the active component I is dissolved in deionized water to form an active component I solution, wherein the molar ratio of calcium nitrate to aluminum nitrate is 1:1 to 1:2; S2, using at least one of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate and cerium nitrate as active component II, dissolving active component II in the active component I solution of step S1, stirring and mixing to form a mixed solution of active components I and II, wherein the molar ratio of active component I to active component II is 1:0.5 to 1:0.1; S3, adding chelating agent citric acid to the mixed solution of step S2, stirring and mixing to form a gel, and then drying to obtain an active substance, wherein the molar ratio of active component I to citric acid is 1:1 to 1:2; S4, the active material of step S3, the microwave absorbing component silicon carbide and the binder bentonite are mixed uniformly according to a certain mass percentage, and ground in a ball mill to obtain a uniformly mixed molding raw material, wherein, by mass percentage, the active material is 60-85%, the microwave absorbing component silicon carbide is 10-30%, and the binder bentonite is 5-10%; S5, the molding raw materials in step S4 are subjected to extrusion granulation and calcination to obtain a composite curing agent.

2. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: The active component I in step S1 is dissolved in 5 to 10 times the mass of deionized water; and / or, the chelating agent citric acid in step S3 is first dissolved in 5 to 10 times the mass of deionized water and then added to the mixed solution in step S2.

3. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: The temperature of the deionized water for dissolving active component I in step S1 is 60-70°C, the temperature of the active component I solution for dissolving active component II in step S2 is 60-70°C, the temperature of the mixed solution in step S3 is 90-95°C, and the drying temperature in step S3 is 105-115°C.

4. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: In step S4, the ball mill has a rotation speed of 300 to 500 r / min and a grinding time of 10 to 30 min.

5. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: In step S5: the particle size of the granulation is 3 to 5 mm; and / or the calcination temperature is 800 to 900° C. and the calcination time is 2 to 4 hours.

6. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: In step S1, the molar ratio of calcium nitrate to aluminum nitrate is 1:1; and / or, in step S2, the molar ratio of active component I to active component II is 1:0.5; and / or, in step S3, the molar ratio of active component I to citric acid is 1:1.5; and / or, in terms of mass percentage, the amount of each component in the molding raw material is: 80% of active material, 15% of absorbing component silicon carbide, and 5% of binder bentonite.

7. The method for preparing a composite curing agent for chlorine-sulfur curing in microwave thermal conversion of polymer waste according to claim 1, characterized in that: In step S2, the active component II is two of zinc nitrate, copper nitrate, iron nitrate, manganese nitrate and cerium nitrate, and the molar ratio is 1:

1.

8. A composite curing agent, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the composite curing agent according to claim 8 for chlorine-sulfur curing in microwave thermal conversion of polymer waste.

Citation Information

Cited By

  • Flue gas sulfur transfer agent as well as preparation method and application thereof

    CN120189954A